Transformasi Pembelajaran Menuju Student-Centered Learning di Era Digital untuk Mengembangkan Kemandirian dan Kreativitas Peserta Didik - Togatorop, Gracesya; Rizkiya, Mutiara; Adistina, Marsita Dwi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
Learning in the digital era faces significant challenges due to changes in student characteristics and the demands of 21st-century skills that can no longer be met through a teacher-centered approach. This situation creates an urgent need to transform learning towards Student-Centered Learning (SCL), where students become the focus of learning activities. This study aims to analyze the implementation of SCL in the digital era in developing students' independence and creativity. This research uses a library research method by reviewing scientific articles, books, and relevant international reports on learning transformation, SCL, digital literacy, as well as the development of students' independence and creativity. The data analysis technique used is content analysis. The results show that SCL supported by digital technology can encourage self-regulated learning through time management, learning planning, and self-evaluation. In addition, student creativity increases through exploration, problem-solving, and project activities that provide space for divergent and innovative thinking. The integration of digital literacy also strengthens students' abilities to access, process, and produce information creatively. Overall, this study confirms that the implementation of technology-based SCL is crucial for developing independent, creative students who are ready to face the challenges of modern education.